Proclamation of the PRC: Reaction of the American Press - Ya. A. Levin (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The article is devoted to the reaction of the American press to such an important historical event as the founding of the People’s Republic of China. The emergence of a new communist state in the East was a great shock and blow to the foreign policy ambitions of the United States, which developed in the logic of a global confrontation with the Soviet Union. China, rich in resources since the end of the 19th century, has been the scene of a constant clash of interests of various states, as a result, on the eve and, especially, after World War II, the two main political forces operating in this territory — the Communist Party of China (CCP) and the nationalist party Kuomintang — found themselves powerful patrons in the form of the USSR and the USA. The topic of the reaction of the American press to the actual failure or, as he later said, was dubbed by numerous experts and publicists who wrote about China — the “loss of China” is an interesting marker of how socio-political thought developed in the American media. American journalists are trying to predict the political consequences of the “loss”, to level the image damage caused to the population by Washington’s foreign policy, to convey the facts and at the same time assess the situation in the region. The study of US press articles will make it possible to better understand the development of American ideas about China and its place in the new paradigm of international relations, to better explore the level of media awareness of this region and the impact that ideas and assessments broadcast by journalists had on society, as well as generally to better understand the initial reaction of American society to the founding of the PRC. Many of the ideas formed at that time remain today an important component of the discursive practices of US public and political life, especially taking into account the complex relations between modern China and the United States.